Proprotein Convertase Subtilisin/Kexin Type 9 and Inflammation: An Updated Review - Wu, Na-Qiong; Shi, Hui-Wei; Li, Jian-Jun (Frontiers in Cardiovascular Medicine, 2022)
The function of Proprotein Convertase Subtilisin/ Kexin Type 9 (PCSK9), a novel plasma protein, has mainly involved in cholesterol metabolism in the liver, while, more interestingly, recent data have shown that PCSK9 also takes part in the modulation of inflammation, which maybe an another explanation for the reduction of cardiovascular risk by PCSK9 inhibition besides significantly its lowering lower-density lipoprotein cholesterol (LDL-C) concentration. Overall, a series of previous studies suggested an association of PCSK9 with inflammation. Firstly, PCSK9 could induce secretion of proinflammatory cytokines in macrophages and in a variety of tissues and elevated serum PCSK9 levels could be observed in pro-inflammatory conditions. Secondarily, detailed pathway studies indicated that PCSK9 positively regulated toll-like receptor 4 expression and inflammatory cytokines expression followed by nuclear factor-kappa B (NF-kB) activation as well as apoptosis and autophagy progression. Moreover, PCSK9 enhanced and interacted with scavenger receptors (SRs) of inflammatory mediators such as lectin-like oxidized-LDL receptor-1 (LOX-1) to promote inflammatory response. Finally, emerging studies also indicated that the role of PCSK9 in atherogenesis was intertwined with inflammation and interaction between PCSK9 and LOX-1 was involved in the inflammatory response of atherosclerosis. Hence, further understanding of the relationship between PCSK9 and inflammation would be necessary for helping to prevent and manage the atherosclerotic cardiovascular disease (ASCVD) clinically. This review article will update the recent advance in the link of PCSK9 with inflammation.